2011
DOI: 10.1155/2011/765923
|View full text |Cite
|
Sign up to set email alerts
|

Blood-Brain Barrier Breakdown Following Traumatic Brain Injury: A Possible Role in Posttraumatic Epilepsy

Abstract: Recent animal experiments indicate a critical role for opening of the blood-brain barrier (BBB) in the pathogenesis of post-traumatic epilepsy (PTE). This study aimed to investigate the frequency, extent, and functional correlates of BBB disruption in epileptic patients following mild traumatic brain injury (TBI). Thirty-seven TBI patients were included in this study, 19 of whom suffered from PTE. All underwent electroencephalographic (EEG) recordings and brain magnetic resonance imaging (bMRI). bMRIs were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
135
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(146 citation statements)
references
References 41 publications
8
135
0
3
Order By: Relevance
“…Of note, such evidence of acute BBB disruption following TBI might predict a population of patients with poor longterm outcome (52). Furthermore, neuroimaging evidence of BBB disruption has been reported in patients following TBI, even after clinically mild or moderate injury; in some cases persisting for years at the site of focal injury (contusions) and with greater frequency in patients with post-traumatic epilepsy (54). Intriguingly, imaging evidence of BBB disruption has been observed in American football participants, independent of clinical evidence of TBI, possibly as a result of exposure to 'sub-concussive' head impacts(55).…”
Section: Page 4 Of 22mentioning
confidence: 99%
“…Of note, such evidence of acute BBB disruption following TBI might predict a population of patients with poor longterm outcome (52). Furthermore, neuroimaging evidence of BBB disruption has been reported in patients following TBI, even after clinically mild or moderate injury; in some cases persisting for years at the site of focal injury (contusions) and with greater frequency in patients with post-traumatic epilepsy (54). Intriguingly, imaging evidence of BBB disruption has been observed in American football participants, independent of clinical evidence of TBI, possibly as a result of exposure to 'sub-concussive' head impacts(55).…”
Section: Page 4 Of 22mentioning
confidence: 99%
“…Shlosberg and associates are of the view that because uncontrolled brain edema usually champions brain herniation which is the main causes of death in patients after TBI [35], early treatment with anti-HMGB1mAb might be a promising strategy for TBI and other complications such as post-traumatic epilepsy [49] and impairment in cognitive function [50]. Guo and colleagues have also indicated that TBI is a risk factor for Alzheimer disease [51].…”
Section: Therapeutic Potentials Hmgb1mentioning
confidence: 99%
“…For the purposes of epilepsy surgery that may occur in the post-traumatic setting, EEG has been co-registered with fMRI for the purposes of improved localization of foci of seizure activity. EEG has also been used to examine TBI-related disruption of the blood-brain barrier (Korn et al, 2005;Tomkins et al, 2011).…”
Section: Other Techniquesmentioning
confidence: 99%